Content of amine nitrogen and hydroxy-proline in the cornea when using an intravenous infusion of cytoflavin in the treatment of alkaline burn (Ukrainian Journal of Ophthalmology, 2026)
Introduction: The actuality of the work is to study the efficacy of infusion therapy of intravenous injection of cytoflavin in the complex therapy of eye burns aimed at stimulation regenerative processes in the cornea .Objective: To study the dynamics of content of amine nitrogen and hydroxyproline in the rabbit cornea using an intravenous infusion of cytoflavin in the treatment of alkaline burn.Material and methods. Investigations were carried out on two groups of rabbits (basic and control), which reproduced the heavy insulated alkaline corneal burn (10 % NaOH with an exposure of 10 seconds) by Chechin's method (1983). The content of amine nitrogen and hydroxyproline in the cornea of experimental animals was determined.Results. The using of cytoflavin in the experimental burn normalizes the concentration of amino acids to 21st days, whereas in the control group (without drug) it is significantly increased only after 45 days. Oxyproline comes almost normal levels in the cornea in the experimental group which used cytoflavin in the period after 21 days.Conclusions: 1.Cytoflavin promotes faster level rise of amino nitrogen in the cornea at experimental burn. The concentration of amino acids in these conditions comes practically normal to 21st days, whereas in the control group (without drug) is significantly increased only after 45 days.2. The normalization of hydroxyproline in the cornea observed in the period after 21 days after the burn in the group of animals who treated by cytoflavin while in the control group of rabbits higher levels of this amino acid observed that may be due primarily to excessive scarring and accumulation of connective tissue proteins in burned cornea.
Keywords: cornea; burn; amino nitrogen; hydroxyproline; cytoflavin